2006
DOI: 10.1063/1.2244480
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ferromagnetism in Co-doped ZnO prepared by thermal diffusion of Co atoms

Abstract: Thermal diffusion was used to dope Co atoms into ZnO single crystal. Particle-induced x-ray emission combined with channeling technique, x-ray diffraction, and ultraviolet-visible light absorption show that Co-diffused ZnO is pure single-phase alloy. The temperature variation of magnetization can be fitted by a linear combination of the Curie law and the Curie-Weiss law with negative Curie-Weiss temperature (−175K). In the high temperature region, the Co-doped ZnO layer is paramagnetic. In the low temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[6] However, many recent studies have shown that Mn 2 + -and Co 2 + -doped ZnO and similar materials are not ferromagnetic. [7][8][9][10][11] Furthermore, room-temperature ferromagnetism has been found to be a universal characteristic of nanoparticles of inorganic material which are otherwise non-magnetic. [12,13] Thus, the ferromagnetism of transition-metal-ion-doped oxides reported in the literature could arise from the nanoparticulate nature of the oxide host.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, many recent studies have shown that Mn 2 + -and Co 2 + -doped ZnO and similar materials are not ferromagnetic. [7][8][9][10][11] Furthermore, room-temperature ferromagnetism has been found to be a universal characteristic of nanoparticles of inorganic material which are otherwise non-magnetic. [12,13] Thus, the ferromagnetism of transition-metal-ion-doped oxides reported in the literature could arise from the nanoparticulate nature of the oxide host.…”
Section: Introductionmentioning
confidence: 99%
“…Though these XRD results indicate the absence of secondary phase or Fe metal clusters, a direct identification of local clusters may rely on the high-resolution transmission electron microscopy or Raman spectroscopy. 13 The paired TM ions ͑mediated by one oxygen ion͒ are expected to have superexchange interaction with each other thus gives rise to an antiferromagnetic behavior. Figure 2 shows the M-H curves of Fe: CeO 2 with different Fe content.…”
Section: Resultsmentioning
confidence: 99%
“…the saturation moment and Curie temperature for Mn doped ZnO ranges from 0.075 μ B /Mn, 400 K [11] to 0.17 μ B /Mn, 30 -45 K [17], respectively. In contrast to these publications, other groups reported the observation of antiferromagnetism [18][19][20], spinglass behavior [21,22], and paramagnetism [19,[23][24][25] in TM-doped ZnO. Recently it was also found that nanoscale precipitates can contribute to the ferromagnetic properties substantially.…”
Section: Introductionmentioning
confidence: 90%